"For Better or Worse": Imagining Innovation in Smart City Municipal Design - Kochever, Kevin M (SJSU ScholarWorks, 2022)
The smart city concept recently (ca. 2010) emerged as a corporate-led system-as-a-service (SaaS) tool to meet city needs of accessibility and efficiency. I looked at three Western cities—Reykjavík, San José, and Toronto—to discover what it meant for city managers to meet municipal needs by embracing smart initiatives. Senior-level city managers, consultants, and technologists invoked vocabularies of smartness and innovation, adopting Internet of Things (IoT) and artificial intelligence (AI) as tools to facilitate human resource and service efficiency needs. I found persistent ambiguity in how city managers described and measured outcomes for city smartness. I also found stakeholders used smartness to participate in global knowledge sharing coalitions with public and private entities, amplifying negotiation potential, and producing values of prestige around novel technological innovation. In so doing, public and private stakeholders formed individual and organizational identities around technological innovation, creating invisible tensions between human resource and technology investments, characterized by celebration of innovation work to the detriment of maintenance labors. My findings inform ongoing scholarship by explaining how smart city technologists sold a discourse of innovation that was not entirely compatible with how cities bureaucratically functioned. Such distinction is important to communicate to scholarly audiences unfamiliar with techno-fetishisms, but familiar with urban management critiques. Moreover, my study opens paths to understanding how private interests influence municipal management through more obscured means.